2010
DOI: 10.3109/09513590.2010.487609
|View full text |Cite
|
Sign up to set email alerts
|

Gynaecologic challenging issues in the management of BRCA mutation carriers: oral contraceptives, prophylactic salpingo-oophorectomy and hormone replacement therapy

Abstract: BRCA1 and BRCA2 mutation carriers have a 54-85% and 45% lifetime risk of developing breast cancer, respectively, and a 18-60% and 11-27% lifetime risk of developing ovarian cancer, respectively. Oral contraceptives (OCs) significantly reduce the risk of ovarian cancer also in BRCA1/BRCA2 mutation carriers. The association between OC use and breast cancer risk in these women is controversial. Some studies showed a modestly increased risk especially among BRCA1 mutation carriers. The risk appears to be greater f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 108 publications
0
13
0
2
Order By: Relevance
“…Female BRCA mutation carriers with breast cancer need counselling on their CBC risk so as to undergo specific surveillance programs or immediate prophylactic surgery (ooferoctomy or mastectomy), radiotherapy or drug treatment (tamoxifen, other hormonal agents or chemotherapy) [12]. Several studies have examined the effect of these options on the risk reduction of CBC [10,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Female BRCA mutation carriers with breast cancer need counselling on their CBC risk so as to undergo specific surveillance programs or immediate prophylactic surgery (ooferoctomy or mastectomy), radiotherapy or drug treatment (tamoxifen, other hormonal agents or chemotherapy) [12]. Several studies have examined the effect of these options on the risk reduction of CBC [10,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Für Frauen mit nachgewiesener BRCA1/2-Mutation wird ein gewisser Anstieg des Erkrankungsrisikos für Brustkrebs angenommen. Dieses dürfte aber durch den Benefit hinsichtlich eines reduzierten Ovarialkarzinomrisikos (Ovarprotektion) aufgehoben werden [8].…”
Section: Ist Orale Kontrazeption Sicher?unclassified
“…There is evidence that teenage (<20 years) [ 64 ] or young adult (<25) [ 65 ] OCP use may increase the risk of BC in women with BRCA mutations, especially BRCA1. Other studies demonstrated increased risk in BRCA1 mutation carriers who used the OCP prior to age 30 [ 66 ].…”
Section: Hormonal Contraception In Brca Mutation Carriersmentioning
confidence: 99%